Fluid flow measurement : a practical guide to accurate flow measurement - LaNasa, Paul J., 1941- (Engineering professional collection, 2014)
Of Contract RequirementsOther Factors in Custody Transfer; Accuracy; Uncertainty; Maintenance of Meter Equipment; Proving Meters; Operation Considerations; Custody Transfer Auditing; Summary of Custody Transfer; Non-Custody Transfer Measurement; Set Point Control Signal; Other Uses; Summary of Flow Measurement; References; 4 Basic Reference Standards; American Gas Association (AGA); Engineering and Operations: Measurement; American Petroleum Institute (API); Determination of Water and Sediment; Basic Calculation Data; Flow Calculation Procedures.